DNA nanostructure-based fluorescent probes for cellular sensing. Issue 11 (6th March 2020) - Kong, Gezhi; Zhang, Meng; Xiong, Mengyi; Fu, Xiaoyi; Ke, Guoliang; Zhang, Xiao-Bing
Abstract : DNA nanostructure-based fluorescent probes for cellular sensing in recent years are summarized and discussed in this review. Abstract : Monitoring the distribution and concentration fluctuation of cellular compositions at the molecular level is of great significance in biological studies and medical diagnostics. Towards this goal, lots of fluorescent probes for cellular imaging have been developed based on different kinds of materials. Among them, newly emerged DNA nanostructures possess the advantages of precisely programmable interactions and predictable thermodynamics, which provide powerful toolkits for the design of fluorescent probes. In this review, the recent advances of DNA nanostructure-based fluorescent probes for cellular imaging are summarized. The preparation and properties of DNA nanostructures were first introduced. Then we focused on the applications of DNA nanostructures for fluorescence biosensing of various kinds of cellular targets, including nucleic acids, proteins, small molecules and physical features. Finally, the current challenges and future directions in the research field are discussed.